Tracing the Mahabharat Thrust (MT) on the basis of lithology and microstructures around Bhainse-Manahari area, central Nepal (Journal of Nepal Geological Society, 2016)
Lithological and microstructural study carried out in Bhainse –Manahari area, central Nepal reveals that the rock sequences of the Bhainse–Manahari area can be divided into two successions: the Nawakot Complex and the Kathmandu Complex. These two Complexes are separated by a distinct thrust boundary, the Mahabharat Thrust (MT). The Nawakot Complex consists of low-grade metamorphic rocks like slate, phyllite, quartzite and limestone while the Kathmandu Complex comprises medium grade (up to garnet grade) metamorphic rocks like garnet-schist, marble and mica-schist. The Mahabharat Thrust (MT) and the Manahari Thrust (MnT) are the two major thrusts in the study area. The MT separates the rocks of the Nawakot Complex (foot wall) in the south from the rocks of the Kathmandu Complex (hanging wall) in the north. The Manahari Thrust in the western part of the study area separates the Dunga Quartzite and the older Benighat Slates lying above it. The microstructure analysis reveals that the rocks in the thrust zone show higher deformation than in the neighboring rocks, and this gradually decreases away from the MT zone. The strain analysis of quartz grains reveals that the rock sequences of the hanging wall of the MT showed pure, simple and complex shear senses and the rocks of the footwall also showed the same pattern indicating MT as a stretching fault.